2021
DOI: 10.47339/ephj.2021.184
|View full text |Cite
|
Sign up to set email alerts
|

Assessing public awareness on the potential health risks of phthalate exposure in plastic consumer products

Abstract: Phthalates are chemical agents used to improve the plasticity of plastic products. Their ubiquitous use in various commercial products results in extensive exposure to humans. Toxicological studies have linked phthalate exposure to developmental and reproductive toxicity, presenting potential health risks. This study investigated the general population on their knowledge and hazard perception of phthalate exposure. The assessment determined if changes in policies or guidelines are needed to minimize potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Additionally, almost two thirds of the respondents were classified into the poor knowledge subgroup because their total score was ≤16. Overall, this fact is supported by Hu and Chen 19 who stated that phthalates are invisible chemicals and several consumers may not be aware of their health risks due to lack of knowledge. Remarkably, socio-demographic characteristics have been demonstrated to influence knowledge.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, almost two thirds of the respondents were classified into the poor knowledge subgroup because their total score was ≤16. Overall, this fact is supported by Hu and Chen 19 who stated that phthalates are invisible chemicals and several consumers may not be aware of their health risks due to lack of knowledge. Remarkably, socio-demographic characteristics have been demonstrated to influence knowledge.…”
Section: Discussionmentioning
confidence: 93%
“…Several factors influence EDC risk perceptions, such as knowledge of and familiarity with EDCs, age, gender, education, and income. For instance, greater knowledge of and familiarity with EDCs is associated with a higher risk perception (Hu & Chen, 2021;Rouillon et al, 2017). Several studies have found a positive association between age and the risk perception of various EDCs, with older adults generally perceiving them as riskier than younger adults (e.g., Brewer & Ley, 2011;Ott, 1990).…”
Section: Control Variablesmentioning
confidence: 99%
“…The rest of the questions were about the general public's knowledge of extreme heat illnesses and how to prevent them. For the analysis, the 'Prefer not to answer' options were omitted due to the potential outlier effect; however, the 'Prefer not to answer' choices in the first three questions were included to show that those results were collected in the survey(17).Descriptive Statistics A total of 70 Canadian participants consented to the survey. The descriptive statistics data was exported and visually presented on pie charts and bar graphs to show the distribution of the responses of each group.…”
mentioning
confidence: 99%